Legal Certainty in the Use of Artificial Intelligence for Healthcare and Medical Diagnosis - Dede Hermawan; Ahmad Jamaludin (Research Horizon, 2025)
The integration of artificial intelligence into healthcare promises to revolutionize medical diagnostics and service delivery. However, rapid technological advancement has outpaced the development of a specific legal framework, creating significant legal uncertainty. This study aims to examine Indonesia’s legal framework for medical artificial intelligence, identify key regulatory gaps, and propose an adaptive legal model to ensure safe and ethical artificial intelligence adoption. Using a normative juridical approach with statutory, conceptual, and comparative analyses, the study finds that current regulations, including Law Number 17 of 2023 on Health and Law Number 11 of 2008 on Information and Electronic Transactions, provide general but insufficient guidance. Critical issues such as liability for artificial intelligence-induced errors, data governance, algorithmic transparency, and patient consent remain unresolved. This regulatory gap poses risks to patients, healthcare providers, and technology developers. The absence of a robust, adaptive legal framework undermines legal certainty and patient protection, limiting trust and safe adoption of artificial intelligence in healthcare. The study proposes a tiered regulatory model based on international best practices to ensure accountability and foster confidence in artificial intelligence-driven medical services.